Development of a Model for Implementing the Afitrah Seller App in the Digital Transformation of MSMe Operations - Ilham Fitrah Anugrah Boer; Anton Mulyono Azis; Irayanti Andriant (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are increasingly required to adopt digital technologies to improve operational efficiency and business sustainability. However, many MSMEs face challenges in sustaining digital transformation after technology adoption due to limited organizational readiness, human resource capabilities, and knowledge management practices. This study aimed to develop an implementation model for the Afitrah Seller application to support MSME digital transformation and enhance operational efficiency. The research employed a Research and Development (R&D) approach using a sequential explanatory mixed-method design. The quantitative phase involved 150 MSME respondents who actively used the Afitrah Seller application, with data analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) through SmartPLS software. The qualitative phase was conducted through semi-structured interviews with academics, IT experts, and MSME practitioners to identify implementation barriers and develop the proposed model. The results showed that technology readiness played a significant role in supporting application implementation, while organizational readiness, human resource capability, and knowledge management required further improvement to ensure sustainable digital adoption. The developed implementation model integrated governance enhancement, employee onboarding, knowledge retention mechanisms, and system optimization strategies. Expert validation confirmed that the proposed model was feasible for implementation within MSME operational environments. This study concluded that successful MSME digital transformation required not only technological infrastructure but also socio-technical alignment involving people, processes, and knowledge management. The findings contributed to the digital transformation literature and provided practical guidance for MSMEs and technology developers in achieving sustainable digital adoption.